A building's thermal assessment using dynamic simulation. Issue 2 (February 2018) - Rodríguez-Muñoz, Norma A; Nájera-Trejo, Mario; Alarcón-Herrera, Olivia; Martín-Domínguez, Ignacio R
A thermal analysis of a two-storey building was made using a dynamic simulation software (TRNSYS). Thermal performance of a 2000 m 2 building was examined by means of several dynamic simulations. The building is located in a region within the BS climate (steppe) according to the Köppen climate classification, where both air cooling and heating are needed to provide comfortable thermal conditions through the entire year. This weather often represents an energy saving challenge, where heat gains and heat losses need to be efficiently managed. A selection of common construction and glazing materials was implemented, and a simple but effective ventilating strategy was tested. Six thermal zones were defined in the building and a comfort temperature range was established as an operating parameter. The results show hourly mean temperatures and energy consumption due to air conditioning throughout a year.